2004
DOI: 10.1080/09583150310001655675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an optical brightener on the development, body weight and sex ratio ofSpodoptera frugiperda(Lepidoptera: Noctuidae)

Abstract: The incorporation of stilbene-derived optical brighteners into baculovirus formulations can substantially enhance virus infectivity and persistence of inoculum in the field. We evaluated the effect of the optical brightener Tinopal UNPA-GX (Sigma Chemical Co.) on the weight, development time, adult emergence and sex ratio of the principal pest of maize in the Americas, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae). Tinopal UNPA-GX was incorporated into semi-synthetic diet at a final concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
(46 reference statements)
2
7
0
Order By: Relevance
“…Destruction of the peritrophic membrane is also reported to effect physiological functions related to digestion and absorption of nutrients 33. This is reflected in the slowing down of growth and increase in duration of the development cycle of the insect observed in the present study and also reported earlier 21, 33. The increased susceptibility of insects fed on diet with Tinopal may have resulted from the physiological stress experienced by the insects owing to digestional disorders induced by Tinopal.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Destruction of the peritrophic membrane is also reported to effect physiological functions related to digestion and absorption of nutrients 33. This is reflected in the slowing down of growth and increase in duration of the development cycle of the insect observed in the present study and also reported earlier 21, 33. The increased susceptibility of insects fed on diet with Tinopal may have resulted from the physiological stress experienced by the insects owing to digestional disorders induced by Tinopal.…”
Section: Discussionsupporting
confidence: 76%
“…Being a stilbene‐derived optical brightener, Tinopal absorbs ultraviolet (UV) radiation and emits visible blue wavelengths 21. Owing to this property, it is reported to bestow photoprotection to microbes when incorporated in the biopesticide formulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optical brighteners such as Tinopal administered in mixtures with occlusion bodies would result in a higher prevalence of covert infection in larvae (Burges and Jones, 1998). Martinez et al (2004) reported that 1 % Tinopal concentration was sufficient to enhance the mortality and hasten the death of Spodoptera frugiperda (Lepidoptera: Noctuidae) larvae. The results revealed that 1 % Tinopal effectively sheltered the POBs from UV degradation and enhanced larval mortality compared to 1 % mango leaf extract 1 % and SNPs.…”
Section: Resultsmentioning
confidence: 99%